2019
DOI: 10.32535/jicp.v2i1.469
|View full text |Cite
|
Sign up to set email alerts
|

Role Analysis of the Power of Reference Groups on the Online Repurchase Intention

Abstract: The development of the internet has a significant impact on business development. Various convenience in conducting transactions has caused more online shops grow in Indonesia. As long as the rapid competition, business people in online stores expect customers to repurchase. Not only service quality and satisfaction are considered in the repurchase intention in the online store, but also it can pay attention to the power of the reference group as one of the considerations for consumers to repurchase.The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The need for the internet is increasing, especially during the pandemic given the restrictions on community activities, so many people -must do various activities from home. The development of the internet has a significant impact on business development (Atmaja & Puspitawati, 2019). Based on statistics from the BPJS, the Indonesian Internet Service Providers Association (APJII) reported that 196.7 million individuals, or 73.7 percent of Indonesia's total population of 266.9 million, were internet users in Indonesia in the second quarter of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The need for the internet is increasing, especially during the pandemic given the restrictions on community activities, so many people -must do various activities from home. The development of the internet has a significant impact on business development (Atmaja & Puspitawati, 2019). Based on statistics from the BPJS, the Indonesian Internet Service Providers Association (APJII) reported that 196.7 million individuals, or 73.7 percent of Indonesia's total population of 266.9 million, were internet users in Indonesia in the second quarter of 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of new digital media has also created new business opportunities and new advertising strategy for marketers. According to Atmaja (2019), The development of the internet has a significant impact on business development. Various convenience in conduction transactions has caused more online shops to grow in Indonesia.…”
Section: Introductionmentioning
confidence: 99%